Hamlet without the prince: the capital approach to development, the New Zealand Treasury's Living Standards Framework and policy making. (1st September 2014) - Engelbrecht, Hans-Jürgen
Abstract : Many governments are going 'beyond GDP' to measure standards of living and to base policy on such wider considerations. One of the more advanced approaches is the Living Standards Framework used by the New Zealand Treasury as a complementary input into the policy process. This paper uses the Framework as a case study to highlight shortcomings and unresolved theoretical and empirical issues in the underlying theoretical model (i.e., the capital approach to development based on mainstream neoclassical economics). In particular, innovation is noticeable mostly by its absence, despite being the main driver of living standards in the long-run. It is argued that innovation should be at the centre of the Framework . Moreover, one must go beyond standard welfare analysis and use a model of the innovation–subjective wellbeing nexus in order to assess the many, potentially very complex, wellbeing implications of innovation. Adoption of such a perspective, although currently resisted by many policy makers, seems to fit well with the 'normative turn' in innovation economics. It does not make one a neo-Luddite. Instead, adoption might help overcome resistance to innovation. This should be especially important at a time when the spread of digital technologies is forecast to cause major societal disruptions.